Sistem Informasi Manajemen Stok Barang Jadi pada Perusahaan PT. ASH Garmen Internasional - JAYA, ALI MAHSUN; Nazar, Syukri (JURNAL TEKNIK INFORMATIKA, 2021)
This research aims to provide information quickly, precisely, and accurately in the process of recording incoming and outgoing goods stock, so that customers can easily get their order information. The type of research is qualitative with Pieces method. This system design is using UML (Unified odeling Language) method. The data collection technique used is by observation and interview. The result of the research is the application can help activities carried out by employees, especially admins in service activities to customers, then the customers can easily look the stock of available products, and then employees can easily update the stock of finished goods without spending so many papers to write on data stock for finished goods.